Cholesterol Crystals in Hepatocyte Lipid Droplets Are Strongly Associated With Human Nonalcoholic Steatohepatitis. Issue 6 (1st April 2019) - Ioannou, George N.; Landis, Charles S.; Jin, Ga‐Young; Haigh, W. Geoffrey; Farrell, Geoffrey C.; Kuver, Rahul; Lee, Sum P.; Savard, Christopher
Abstract : It is unclear what drives the development of fibrosing nonalcoholic steatohepatitis (NASH). We aimed to determine whether cholesterol crystallization within hepatocyte lipid droplets (LDs) distinguishes patients with fibrosing NASH from patients with isolated hepatic steatosis and to study pathways leading to cholesterol accumulation in hepatocyte LDs . Patients with fibrosing NASH (n = 16) were compared to patients with isolated steatosis (n = 14). Almost all patients with fibrosing NASH had free cholesterol staining by filipin (16/16) and cholesterol crystals (15/16) in hepatocyte LDs, mostly in association with the LD membrane, compared to only 3/14 with cholesterol crystals and 3/14 with faint filipin staining in patients with isolated steatosis ( P < 0.05). We were unable to identify significant differences in the expression of genes in liver tissue related to cholesterol homeostasis or LD proteins between patients with fibrosing NASH and isolated steatosis. Human hepatoma cell line (HepG2) cells were supplemented with low‐density lipoprotein (LDL)‐cholesterol and oleic acid to develop large LDs, similar to those observed in patients with NASH. Fluorescent markers were used to track the uptake and intracellular trafficking of LDL‐cholesterol. LDL‐cholesterol was taken up by HepG2 cells and transported through the endosomal‐lysosomal compartment directly to LDs, suggesting direct contact sites between late endosomes and LDs. Exposure of HepG2 cells to LDL‐cholesterol resulted in a high concentration of cholesterol and cholesterol crystallization in LDs. Conclusion: Excess cholesterol is stored in the liver primarily within hepatocyte LDs where it can crystallize. Our findings are best explained by direct transport of cholesterol from late endosomes/lysosomes to LDs in hepatocytes. We found a strong association between the presence of LD cholesterol crystals and the development of fibrosing NASH in humans, suggesting a causal relationship. Abstract : Excess body cholesterol is transferred to hepatocyte lipid droplets for storage, where it can crystallize. Our findings are best explained by direct transport of cholesterol from late endosomes/lysosomes to LDs in hepatocytes. When cholesterol crystallizes in hepatocyte lipid droplets, it may drive the development of fibrosing NASH.